Ecosystem-Based Management Revisited Using Physico-Chemical Factors Interactions with Fish Resources of Lake Malombe, Malawi - Msiska, Orton V.; Singini, Wales; Phiri, Titus B. (European Journal of Applied Sciences, 2025)
Lake Malombe is one of the “hotspot” freshwater ecosystems in Malawi which has attracted both local and international scientists primarily due to changes in fish and ecosystem services. The lake has suffered from overfishing with catches declining from > 12,000 tones in 1980s to 3,820 tons in 2016, creating a gap in fish supply that has affected the livelihoods of many fishers. A concomitant decline in fish taxa was registered from 56 to 28; however, the full ecological impact has only recently been assessed through a series of synchronized studies on the benthos, limnology and fish species. This study shows interactions of how locally induced human activities have been compounded by Global Climate change at interannual scale. An exotic snail from Asia, Melanoides tuberculata, is also implicated in the change of fauna to the extent that its population now forms more than 40% of fish by-catches. The phytoplankton concentrations of 2.1-13.4µg/L were recorded while zooplankton varied between cool season (35,387-43,545 individual/m3) and hot dry season (10,399-171,323 individual/m3). Carbon fixing in the pelagic zone was estimated at 65.0-873g per m2 contributing to high carbon sequestration. This has led to need to hatchery-reared introduction of a molluscivorous fish species, Trematocranus placodon, tilapias (Oreochromis karongae) and Bathyclarias loweae to utilize snails and neutralize plankton taking advantage of the high amounts of matter captured in the system. Drawing from examples from other eutrophic systems, “Pen Culture” seems to be an appropriate technique given the shallowness of the water levels and need to utilize rich benthic fauna. Furthermore, this is a carbon sink that should contribute to national carbon units. Since the bulk of national hydropower and irrigation investments are located downstream, in situ fish production would maintain required water flow; most importantly, continued monitoring studies should be synchronized with water level controls at the Shire Barrage to mitigate negative downstream impacts. The decline in maximum water depth from 7.0 meters in 1993 to 5.6 meters in 2017, accompanied by changes in shoreline configuration, caused by increased catchment sedimentation. Thus, soil and agriculture conservation, forestry and hydrology studies are critical for sustenance of the Lake Malombe ecosystem. Effective management should be holistic taking a broader multidisciplinary approach involving all concerned. There is need for some more serious engagement by a cross-section of scientists to assist in resolving the challenges and dilemma that Lake Malombe poses to Malawian society. A mix of fisheries and aquaculture innovations could uplift fish production to more than 6,000 tons annually and serve as test case for application of a series of techniques to similar water bodies. We advocate for the consideration of “Pen Culture” in efforts in restoration of fisheries.